A oralidade como estratégia de interação na escrita: o caso do jornal Agora São Paulo - Pandorf, Analu (2011)
This work has as objective the study of orality in writing. To investigate this subject, the object of our study will be constituted by the newspaper Agora São Paulo, from the journalistic enterprise Folha da Manhã S/A. Our hypothesis is that this newspaper, in terms of its readership, builds their texts with features reminiscent of our resources of oral communications. In other words, we assume that specific forms of layout and determined linguistic-dicoursive choices in the elaboration of texts remind the construction of face to face interactions. Although the object of this study is the newspaper Agora São Paulo, along with its analysis, it is also focused on the newspaper Folha de S. Paulo, from the same journalistic enterprise. The reason of this approach, when comparing both newspapers, is to give more evidence to the traces of orality in the first. The research objectives are: to identify the linguistic and discoursive resources used for the atribution of the orality in the newspaper Agora São Paulo; to point out the possible reasons that would lead this newspaper to mark its texts with traces of orality and, consequently, the newspaper Folha de S. Paulo to prevent these traits or to insert them less frequently in their texts; and, finally, to define, based on the presence of a greater or lesser degree of orality in the texts of both newspapers, the profile of the readers of these newspapers, particularly the readers of the newspaper Agora São Paulo. The theoretical basis for the development of this study aims on the theory of enunciation. The enunciation is the act of producing an utterance (text) made by a speaker (author), who, through this product (the text), communicates with an enunciatee (reader). In the statement, that is, in the text, there are the strategies used by the speaker to act over the enunciatee. In the view of enuncaition, the orality revealed in enunciative texts, that is, those in which there are traces of me, here and now in the act of enunciation. The absence of these traits or erasures features the text that, in principle, does not evoke traces of orality. The completion of this study may contribute to better understand the reasons and functions of the use of oral strategies in the construction of written texts and thereby help the teacher in the effort to guide students in analyzing and interpreting texts.